Detection of pesticide using the large stokes shift of luminescence of a mixed lanthanide co-doped metal–organic framework. (15th January 2019) - Singha, Debal Kanti; Majee, Prakash; Mondal, Sudip Kumar; Mahata, Partha
Graphical abstract: A lanthanide co-doped (Eu 3+ and Tb 3+ ) yttrium based metal–organic framework has been synthesized through isomorphous substitution strategy in a three-dimensional MOF using solvothermal procedure. This MOF shows luminescence based sensitive and selective detection of azinphos-methyl pesticide over the other analytes in aqueous medium with detection limit of 212 ppb. Abstract: For the utilization of large stokes shift and low self quenching of luminescence, we have successfully constructed a luminescent europium and terbium co-doped yttrium based metal–organic framework [Y1.8 Eu0.1 Tb0.1 (PDA)3 (H2 O)1 ]·2H2 O (where PDA = 1, 4-phenylenediacetate), 1, through isomorphous substitution strategy in a three-dimensional yttrium based MOF using solvothermal method. The structure and size of1 was systematically characterized by PXRD, TGA, SEM and EDX analysis. On the exposure to UV light, the aqueous dispersion of1 exhibits light green emission in the visible region. This emissive property was employed for the highly sensitive and selective detection of azinphos-methyl pesticide in aqueous medium through luminescence quenching for the first time. Using this compound ppb level detection of azinphos-methyl has been achieved.